Retrograde Fixation of the Ulna in Pediatric Forearm Fractures Treated With Elastic Stable Intramedullary Nailing - Papamerkouriou, Yvonne-Mary (Cureus, 2020)
Introduction This study analyzes the outcomes of retrograde fixation of the ulna in pediatric forearm fractures treated with elastic stable intramedullary nailing (ESIN). Materials and Methods A retrospective analysis was conducted by reviewing patient records of forearm fractures treated with ESIN by retrograde fixation. The study included 30 children (26 boys and 4 girls). The mean age at the time of injury was 11.7 years (range: 6.6 to 14.3 years). The technique is described. All patients were followed up until hardware removal. Results The mean time for fracture healing was 5.3 weeks (range: 4 to 8.8 weeks). The mean time for nail removal was 6.6 months (range: 5 to 10 months). There were five cases with rotation deficits, one of which was a re-fracture. Conclusions When antegrade nailing is performed, the ulna is sometimes complicated by non-union as well as entry point irritation. We did not encounter such complications. Retrograde fixation of the ulna in pediatric forearm fractures treated with ESIN is a safe and effective alternative to common fixation (antegrade ulnar fixation) and offers technical advantages.